Pengaruh Kualitas Sistem, Kualitas Informasi dan Kemudahan Penggunaan terhadap Kepuasan Pengguna Sistem Informasi Keuangan Akademik di Akademi Maritim Nusantara Cilacap - Indriyani Indriyani; Tiara Pandansari; Frilia Esti Anggraeni (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
The Academic Financial Information System is one of the information systems used to improve services to cadets related to finance. This study aims to determine the effect of system quality, information quality, and ease of use on user satisfaction of the Academic Financial Information System at Akademi Maritim Nusantara Cilacap. The object of this research is the active cadets of the Nusantara Maritime Academy Cilacap who are users of academic financial information systems. The research was conducted at the Nusantara Maritime Academy Campus Cilacap using quantitative methods, with a random sample of 128 people. Data collection was carried out using a Likert Scale model statement sheet that had been tested. The analytical technique used in this research is correlation, multiple linear regression, t test, F test and determination of R square. This study partially shows that the system quality variable has no positive and significant effect, the information quality variable and user convenience have a positive and significant effect on user satisfaction. Simultaneously, system quality, information quality and ease of use have a positive and significant effect on User Satisfaction with Academic Financial Information Systems in Nusantara Maritime Academy.